(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2021)
The paper deals with the history of studies of the Dniepr-Donets valley aquatic and wetland flora. This article covers the period of 18 and 19 centuries. According to the results of the study , the first reliable data about aquatic and wetland flora dated mid-late 17th century. I. Guildenstendt and D.I. Bagaliy published the fragmentary data on the flora composition of Slobidska Ukraine from the end of the 16th to the beginning of the 17th century. The new stage of botanical studies in the region was connected with the foundation of the Kharkiv University in 1804. K.F. Ledebur published "Flora Rossica sive enumeration plantarum in totis Imperi Rossici provincis Europaeis, Asiaticia et Americanis hucusque observatarum" in 1842–1853. It also contains some data for the small part of the Kharkiv province. The first fundamental monograph is "Conspectus plantarum…", published in 1859 by V.M. Chernjajev. The list includes 1769 species. The Natural Researchers Society was founded in 1869 in Kharkiv University. The members of this organization provided numerous botanical expeditions. The analysis of literature sources of 19th century revealed thatthat despite the active study of flora and vegetation of the region, or its individual administrative territories we do not know any specialized floristic work on the study of flora and vegetation of water bodies and wetlands. However, the analysed publications contain important historical information on the distribution of rare regional species. Most of them are currently either extinct or critically endangered, e.g. Calla palustris, Callitriche stagnalis, Drosera rotundifolia, Ledum palustre, Limnanthemum nymphoides, Trapa natans, Oxycoccus palustris etc. Thus, the period from the end of the 16th to the end of the 19th century is a period of the floristic researches of the Kharkiv region and adjacent territories. The main researchers were V.M. Chernjajev, I. Kovalevsky, K.S. Gornytsky, V.I. Taliev, P.M. Nalyvaiko with the exception of some works in a new area of research – applied, which began to appear only in the late 19th century.